Food allergy knowledge and attitude of restaurant personnel in Turkey. Issue 2 (13th October 2014) - Sogut, Ayhan; Kavut, Ayşe Baççıoğlu; Kartal, İbrahim; Beyhun, Ercument Nazim; Çayır, Atilla; Mutlu, Mehmet; Özkan, Behzat
<x xml:space="preserve">Abstract</x> Background The incidence of food‐induced allergic reactions is gradually increasing. Most of these allergic reactions occur in restaurants. Therefore, this study aims to investigate the awareness of restaurant personnel about food allergy. Methods The training, knowledge levels on food allergy, and comfort level in providing safe food of 351 restaurant personnel in Erzurum Province, Turkey, were assessed through a face‐to‐face survey. Results Among the participants, 81.5% were male (mean age 28.5 ± 8.5 years). Among them, 17.1% were chefs, 11.1% managers, 5.7% owners, and 66.1% waiters. Food allergy training was reported by 17.1% of the participants. The rates of restaurant personnel who gave the correct answers to the 4 questionnaire items, "Customers with food allergies can safely consume a small amount of that food/Food allergic reaction can cause death/If a customer is having an allergic reaction, it is appropriate to immediately serve them water to 'dilute' the allergen/Removing an allergen from a finished meal (eg, taking off nuts) may be all that is necessary to provide a safe meal for an allergic customer, " which measure food allergy knowledge levels, were 46.4%, 65.7%, 55.0%, and 65.7%, respectively. Conclusion According to our study, there are gaps in the food allergy knowledge of restaurant personnel. Because preparing and serving safe meals to patients with food allergy in restaurants is important, the training of restaurant personnel in food allergy is necessary.